PENERAPAN MEDIA PINGUIN PINTAR BERBASIS MODEL PROBLEM BASED LEARNING UPAYA PENINGKATAN KEMAMPUAN MENULIS KELAS II - Dhiva Nabiilah Azaria; Panca Dewi Purwati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Students’ difficulties in using capital letters and punctuation correctly indicate the need for interactive and problem-based learning media. The purpose of this study is (1) to describe the implementation steps of the Pinguin Pintar educational game media based on Problem Based Learning (PBL), and (2) to describe the effectiveness test of this media in improving students’ writing skills, especially in the use of capital letters and punctuation. This study employed a mixed-method Sequential Explanatory design referring to Khabibullah & Sholahuddin’s (2024) theory, beginning with quantitative analysis followed by qualitative exploration. The results show a significant improvement in students’ writing ability, marked by an increase in the average score from 74.5 to 86.1 and a rise in classical completeness from 42.8% to 86.4%. Improvements were also seen in specific writing aspects: initial capital letters (87.5%), capital letters for proper names (84%), accuracy of periods and commas (77.2%), and question marks (82.5%). Based on the two research objectives, it is concluded that (1) the Pinguin Pintar media can be implemented systematically through PBL stages such as problem orientation, investigation, discussion, and solution presentation, and (2) the media is proven effective in improving students’ accuracy in using capital letters and punctuation.